PENGARUH LEVERAGE, FIRM SIZE, DAN LIQUIDITY TERHADAP FINANCIAL PERFORMANCE - Revata, Lifia Nanda; Sudirgo, Tony (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to obtain empirical evidence regarding the effect of Leverage, Firm Size, and Liquidity on Financial Performance in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This research used 76 samples and 228 data from manufacturing companies selected by purposive sampling method. The data in this research were inputted and calculated using the Microsoft Excel program and processed using the Eviews 10 program. The results of this study indicate that liquidity has a significant negative effect on financial performance, leverage has a nonsignificant negative effect on financial performance, and firm size has a nonsignificant positive effect on financial performance.